Clothing Aesthetics In Russian And English - Azimova Nozima Hikmatovna; Kobilova Nargisa Sulaymonbekovna (Genius Journals, 2022)
The article discusses some peculiarities of clothing aesthetics in the Russian and English languages. It also deals with the study of names denoting garments, the essential aspects of the development of a particular national culture.
Keywords: Names of garments; consumer clothing; vocabulary of clothing; fashion